Water, sanitation, and hygiene service inequalities and their associated factors among urban slums and rural communities in Eastern Ethiopia - Mekonnen, Getachew Kabew; Zako, Abdurauf; Weldegebreal, Fitsum; Desalew, Assefa; Raru, Temam Beshir; Umer, Ukash; Urgesa, Kedir (Frontiers in Public Health, 2024)
Background Understanding the level of inadequate water, sanitation, and hygiene (WaSH) services in urban and rural settlements is crucial for prioritizing community interventions and resource allocation. However, there is a lack of evidence regarding discrepancies in WaSH services across rural and urban slum communities in Ethiopia. Objective This study aims to assess inequalities in households’ WaSH services and their associated factors among urban slums and rural communities in Eastern Ethiopia from February to April 2024. Methods A comparative community-based cross-sectional study design was conducted, with study participants selected through stratified random sampling using proportional-to-size allocation. Data were entered into Epi Data version 3.1 and then exported to STATA version 17 for analysis. Bi-variable and multivariable logistic regression was conducted, and associations were reported as odds ratios (ORs) with 95% confidence intervals (CI), using a p-value less than 0.05 as the significance threshold. Result A total of 278 urban and 301 rural households participated in the study, with a response rate of 94%. Key indicators showed that WaSH services were significantly better in urban areas compared to rural households. For example, 98% (95% CI: 96, 99) of urban households had access to an improved water source compared to 76% (95% CI: 71, 80) of rural households. The proportion of households with improved latrines was 44% (95% CI: 38, 50) in urban areas and only 14% (95% CI: 11, 19) in rural areas. Handwashing practices at all five critical times were reported by 52% (95% CI: 46, 58) of urban household heads, compared to 22% (95% CI: 18, 27) of rural households. Additionally, occupation (such as being a farmer, p = 0.000) and water service satisfaction (p = 0.000) were significantly associated with these key WaSH outcomes. Conclusion The study revealed that the WaSH services in urban slums are considerably better than in rural households. Socioeconomic factors significantly influence the existing disparities in WaSH services. Stakeholders should focus on providing targeted, strategic support to communities to address the challenges in WaSH service provision.